(untitled) (Third Sector Social Economic Review, 2025)
Learning styles are individual approaches that determine how individuals perceive, process and remember information. Kolb’s learning styles model identifies four main learning styles: Diverger, Converger, Assimilator and Accommodator. These styles are used in educational processes to understand how students can learn more efficiently and guide the adaptation of teaching methods. Learning styles play an important role in designing teaching strategies, identifying individual learning needs and improving students’ performance. In addition, teachers need to develop various teaching methods by considering these styles for students to learn more effectively. This study aims to examine the learning styles of tourism undergraduate students of universities in Çankırı, Kastamonu and Sinop provinces located in TR 82 region of Turkey. The research was carried out by questionnaire method using Kolb’s learning styles inventory. Data were collected from 535 students in total and demographic characteristics and learning styles of the students were analysed. The results of the research showed that there was no significant difference in learning styles according to gender, high school type and grade level, while significant differences were observed on the basis of university and department. Analyses between universities revealed that learning styles varied according to the university studied, and similar differences were found between departments. These findings emphasise that teaching methods at university and department level should be diversified according to students’ learning styles.